Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,369 questions

17,804 answers

1,438 comments

36,292 users

Using the Gauss-Jordan method solve :

0 votes
x + 5y - z = -4
3y - z = -1
-3x + 6y + 2z = 11
asked Mar 18, 2014 in ALGEBRA 2 by chrisgirl Apprentice

1 Answer

+1 vote

Given equations are + 5 - z  = -4 ---> (1)

3y  - z  = -1 ---> (2)

-3 + 6 + 2= 11 ---> (3)

Write the equations into matrix form AX  = D.

A  is Coefficient matrix , X  is Variable matrix and D  is constant matrix.

Now we solve the equations in Gauss-Jordan method.

image

The augmented matrix is [AD ]

image

image  are represents first row ,second row and third row .

image

image

image

image

image

image

image

Solution :

image

answered Mar 21, 2014 by david Expert

Related questions

...